The excellence scholarships program: Analysis of implementation aspects and societal impact - Abdul Basit; Achmad Kosasih; Nurzela Eka Juniarfa; Yusuf Fadli; Adie Dwiyanto Nurlukman (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
Education creates reliable and competitive people resources, which determines a nation's success. Scholarship policies have a substantial impact on the growth of a nation, particularly in terms of enhancing the quality of human resources and access to quality education. Open access to education can help establish an improved education system. The Excellence Scholarships Program is part of the Indonesian government's goal to produce trustworthy and competitive human resources. This research used a qualitative descriptive methodology by tracing official government documents associated with the Excellence Scholarships program. This report analyzes the 2019-2020 implementation and impact of Indonesia's main scholarship program.  This study examined program implementation using descriptive-qualitative research. According to the findings of this study, 2025 undergraduates won scholarships in the last two years. The procedures and aid distribution of the Excellence scholarship program are effective because they adhere to the predetermined flow and conditions, however, future improvements are required for the implementation of these scholarship programs: first, improving the principle of equal distribution of scholarship recipients to combat inequality, particularly in eastern Indonesia; and second, providing equal opportunities. This research also suggests further research could look into how the excellence scholarships program enhances scholarship recipients' quality of life and human resources.